Explaining local self-government reorganisation in Croatia : the garbage can model of decision-making - Menger, Mariza (Array, 2019)
This article deals with changes to the system of local and regional self-government in Croatia between 2003 and 2017. For the most part, reform efforts, excluding some positive developments with regard to the promotion of the democratic principles of governance, have not been successful. The article addresses the question of how to theoretically account for these changes. The aim is to offer an understanding of reform failure by focussing on the preceding processes. The article begins by establishing that reform efforts in the existing literature on Croatian local- and middle-level government reorganisation have predominantly been explained either by means of the rational-instrumental perspective or the power and conflict perspective. The former argues that reorganisation outcomes are a product of rational decision-makers, who in the early 1990s and afterwards sought to, for one reason or another, establish centralistic administration of public affairs. The latter, on the other hand, proposes that the current local- and middle-level government structure is a direct reflection of the power structure of the current constellation of political actors. The article goes on to suggest that, at least in part, changes made to the system can be attributed to the garbage can model of decision-making. This is due to the fact that participation in the decision-making arena throughout this period was fluid, the decision-makers’ attention scarce and their goals ambiguous, and the definitions of the problems unclear.